Contribution à l'étude de virus de mollusques marins apparentés aux Iridoviridae et aux Herpesviridae - Le Deuff, Rose-marie (Université de Bordeaux II, 1995)
Among the marine molluscs, Pacific oyster, Crassostrea gigas, is actually the most reared species in the world. Noticeably in France, where it was imported between 1960 and 1970, and replaced Portuguese oyster, Crassostrea angulata. Intensification of breeding and the associated introductions of new species may be hazardous. Indeed, they might be responsible for the appearance and the dissemination of new diseases in bivalve molluscs. In addition to these observations, the quasi monobreeding of C. gigas in France enhances the necessity to develop research concerning the diagnosis of pathologies affecting this species, namely the diagnosis of viral diseases. Several families of viruses have been described within marine bivalves molluscs. The purpose of this work fits particularly with iridovirus-like and herpesvirus-like. ln a first part, different axis of work were centered round the objective to develop methods for the diagnosis of iridoviruses. Noticeably, the existence of common antigens between fish and oyster related viruses was checked. The second part of this work consisted in the study of herpes-like viruses associated with mortalities of larval and spat C. gigas. A descriptive part is followed by the demonstration of the pathogenic nature of the virus, in experimental reproduction of the disease on larval stages of C. gigas. Several attempts were also performed concerning the fields of virus expression and transmission in vivo, and virus propagation in vitro. Finally, different axis of work, centered round the development of diagnosis methods, were developped. Particularly, virus particles were purified from infected larvae. L'huître creuse, Crassostrea gigas, est aujourd'hui une des espèces de mollusques marins les plus élevées dans le monde. Notamment en France, où elle a été importée dans les années 60-70, et a remplacé l'huître portugaise, Crassostrea angulata, espèce décimée à cette époque par des iridoviroses. L'intensification des élevages et les introductions de nouvelles espèces qui y sont ...